The Naturalness of Translation in Translating Short Story Entitled â€œDrupadiâ€ from Indonesian into English - Dewi, N L.P.V.; Mardjohan, Asril; Santosa, Made H (Lingua Scientia, 2016)
This study aimed at analyzing the naturalness of translation and finding the percentage of the naturalness of translation in translating short story entitled â€œDrupadiâ€ from Indonesian into English. The subjects of this study were two native speakers which are come from the native area. Meanwhile, the object of this study was a short story entitled â€œDrupadiâ€ especially the sentences in both Indonesian and English version. In this study, the researcher used Larsonâ€™s theory as the reference of the study in order to analyze the naturalness of translation in short story entitled â€œDrupadiâ€ from Indonesian into English. The data were obtained by two methods of data collection, namely checklist and interview. The total of the data in this study was 131 sentences and it was analyzed descriptively. The result of this study showed that, 0% of the data is considered to fall into â€œunnaturalâ€ level, 2.29% are considered to fall into â€œless naturalâ€ level, 13.74% of the data belong to the â€œnaturalâ€ level, and 83.97% of the data is classified as â€œhighly naturalâ€. Based on the result, it can be concluded that the short story entitled â€œDrupadiâ€ which has been translated by Tom Hunter from Indonesian into English was in â€œhighly naturalâ€ level and it can be used as teaching material for the teacher who teaches language, especially translation.